PENGARUH METODE DIFERENSIASI TERHADAP PRESTASI BELAJAR DI MAN 1 KOTA MAKASSAR - R, St. Amaliah; Mustamin; Wahab, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the differentiated learning method on the academic achievement of Grade X students in the Akidah Akhlak (Islamic Creed and Ethics) subject at MAN 1 Makassar City. The study employs a quantitative approach with a correlational research design. The population consisted of 382 Grade X students, while the sample comprised 195 students determined using Slovin's formula and proportional random sampling. Data collection techniques included questionnaires, tests, and documentation. Data were analyzed using multiple linear regression with the aid of SPSS software, encompassing validity tests, reliability tests, classical assumption tests, t-tests, F-tests, and the coefficient of determination (R²). The results indicate that, individually, all dimensions of the differentiated learning method have a positive and significant effect on student academic achievement. Content differentiation (X₁) yielded a regression coefficient of 0.69359, a calculated t-value of 11.21, and a significance level of 0.000; process differentiation (X₂) showed a regression coefficient of 0.08211, a calculated t-value of 2.05, and a significance level of 0.041; product differentiation (X₃) showed a regression coefficient of 0.08486, a calculated t-value of 1.98, and a significance level of 0.049; while learning environment differentiation (X₄) showed a regression coefficient of 0.09955, a calculated t-value of 2.18, and a significance level of 0.031. Simultaneously, the differentiated learning method significantly influenced student academic achievement, with a calculated F-value of 52.84 and a significance level of 0.000. The coefficient of determination (R²) of 52.7% indicates that the differentiated learning method accounts for 52.7% of the variation in student academic achievement, while the remaining 47.3% is influenced by factors outside the scope of this study. Based on the research findings, it can be concluded that the differentiated learning method has a positive and significant impact on the academic achievement of Grade X students in the Akidah Akhlak (Islamic Creed and Ethics) subject at MAN 1 Makassar City. Therefore, it is recommended that teachers implement differentiated learning optimally to ensure the learning process is effective and student-centered, and capable of enhancing academic achievement in alignment with the needs, interests, and characteristics of each student.